Fishery, population characteristics and yield estimates of coastal tunas at Veraval - Ghosh, Shubhadeep; Pillai, N G K; Dhokia, H K (Indian Journal of Fisheries, 2016)
The fishery, population characteristics and yield estimates of coastal tunas Thunnus tonggol, Euthynnus affinis and Auxisthazard at Veraval were studied during 2003 – 2006. The average annual catch was 731 t, which contributed to 28% to thetotal gillnet catches. The main species of tunas landed were T. tonggol (46.8%), E. affinis (17.5%), Thunnus albacares(6.4%) and A. thazard (5.2%). E. affinis and A. thazard exhibited isometric growth but for T. tonggol it was allometric. Thevon Bertalanffy growth equation was Lt = 107.4 [1 – e - 0.18 (t + 0.0729)] for T. tonggol, Lt = 72.5 [1 – e - 0.56 (t + 0.0327)] for E. affinis andLt = 46.6 [1 – e - 0.93 (t + 0.0153)] for A. thazard. The mortality rates M, F and Z for T. tonggol were 0.4, 0.72 and 1.12 respectively,while for E. affinis and A. thazard, the values were 0.94, 1.48 and 0.75 and 4.49, 1.69 and 5.97, respectively. The exploitationratios for T. tonggol, E. affinis and A. thazard were 0.64, 0.44 and 0.75 respectively. The higher exploitation rate and lowerMSY in T. tonggol and A. thazard was an indication of intensive fishing and overexploitation of these speceis. But forE. affinis, the exploitation rate was low and MSY was high indicating further scope for exploitation. Reducing the presentfishing effort by 40%, maximum relative yield was realized for T. tonggol and A. thazard but for E. affinis, increasing thefishing effort by 80% provided the maximum relative yield.